The application of realistic mathematics education approach: Enhancing students’ understanding of mathematical concepts through algebra board media - Dania, Mohammad Rifsan; Samura, Asri Ode; Djawa, Yani (Mahesa Research Center, 2025)
This study investigates the impact of the Realistic Mathematics Education (RME) approach, utilizing algebra board media, on students’ comprehension of mathematical concepts. The research design employed a Nonequivalent control group. The research subjects consisted of 40 students from State Junior High School 8 South Halmahera, Indonesia. The findings demonstrated that the implementation of RME with algebra board media significantly enhanced students’ ability to grasp mathematical concepts. The t-test yielded a Sig. (2-tailed) value of 0.000 (p < 0.05), rejecting H0 and accepting Ha, indicating a substantial effect. The Effect Size value of 2.52 signifies a “large” effect. The N-gain analysis of the average score of 0.72 (71.84%) indicates that this approach is “quite effective” in augmenting students’ understanding of mathematical concepts, aligning with the RME principle of connecting mathematics to reality and facilitating the concrete representation of abstract concepts.